2012
DOI: 10.1111/j.1477-2574.2012.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

The safety of a pancreaticoduodenectomy in patients older than 80 years: risk vs. benefits

Abstract: As 30-day mortality and survival are similar to those observed in younger patients, a PD can be offered to carefully selected octogenarians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 12 publications
2
64
4
1
Order By: Relevance
“…8 Melis et al also reported that the OS was 13.1 months in the patients who were less than 80 years of age and 17.3 months in the patients who were 80 years of age or older after a median follow-up of 35 months. 9 On the contrary, Oliveira-Cunha et al reported that the OS was 57.3 months in the patients who were less than 70 years of age and 78.7 months in the patients who were 70 years of age or older (P , 0.001).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…8 Melis et al also reported that the OS was 13.1 months in the patients who were less than 80 years of age and 17.3 months in the patients who were 80 years of age or older after a median follow-up of 35 months. 9 On the contrary, Oliveira-Cunha et al reported that the OS was 57.3 months in the patients who were less than 70 years of age and 78.7 months in the patients who were 70 years of age or older (P , 0.001).…”
Section: Discussionmentioning
confidence: 92%
“…20 In contrast, Melis et al evaluated the short-term outcomes and longterm survival after PD for pancreatic adenocarcinoma in 200 patients and divided them into 2 groups using a cutoff value of 80 years old. 9 They reported that overall morbidity and length of postoperative stay were increased in elderly patients compared with younger ones (44.0% versus 68.0%, P ¼ 0.03 and 13.7 versus 20 days, P ¼ 0.01, respectively). These data suggest that when complications occur in elderly patients, they rapidly increase in severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some authors have found similar complication rates between groups, others have shown that elderly patients usually have longer stay in the intensive care unit (ICU) and require more readmissions after PD (4)(5)(6). Recent publications are focused in establishing perioperative factors associated with overall morbidity and classifying severity of the complications, as mild ones have little clinical significance (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Tailor S. Ryall has summarized the studies regarding the long-term outcomes following pancreatoduodenectomy for PDAC in different age groups to show a tendency toward decreased survival among the elderly patients [3,4,5,6,7,8,9,10,11]. However, factors influencing long-term survival in elderly were not depicted.…”
Section: Introductionmentioning
confidence: 99%